Mirrored OLED pixel circuit for threshold voltage and mobility compensation with IGZO TFTs. Issue 10 (October 2015) - Liao, C.; Deng, W.; Song, D.; Huang, S.; Deng, L.
Abstract In this paper, pixel circuit using mirroring structure with Indium–Gallium–Zinc oxide (IGZO) thin film transistors (TFTs) for active matrix organic light emitting diode (AMOLED) display is proposed. This pixel circuit consists of only four TFTs, and one capacitor. Due to the mirroring structure, characteristic of the driving TFT can be precisely sensed by the sensing TFT, which is deployed in a discharging path for gate electrode of the driving TFT. This discharging process is strongly dependent on threshold voltage (VT) and effective mobility of the sensing TFT. Circuit operating details are discussed, and compensation effects for threshold voltage shift and mobility variations are verified through numerical derivation and SPICE simulations. Furthermore, compared with conventional schematics, the proposed pixel circuit might have much simplified external driving circuits, and it is a promising alternative solution of high performance AMOLED display.